Genital ulcer diseases among HIV_infected female commercial sex workers in Ibadan, Nigeria (2011)
We evaluated the prevalence and association of Genital Ulcer Diseases (GUDs) among HIV-1 infected female commercial sex workers (FCSWs) in Ibadan, Nigeria. A total of 250 FCSWs from brothels in Ibadan were tested for presence of antibodies to HIV and Syphilis. Pelvic examinations for signs of sexually transmitted infections (STIs) were carried out on the subjects. Endocervical and high vaginal swabs were collected from each of the subjects to establish laboratory diagnosis of STIs. Their age ranged from 15 to 55 years (Mean = 25.8 yrs; SD = 3.74). Majority (246/250) were Nigerians, while 1.6% were from neighboring West African countries. Sixty four (25.6%) of the subjects were positive for HIV-1 while seven (2.8%) had dual HIV-1/2 infection. Analysis of the STIs showed that 49 (19.6%) of the CSWs had GUDs. Herpes genitalis was the commonest GUDs as it occurred in 25 (10%) of the subjects. Other STIs identified were chancroid (5.6%), syphilis (4.0%) and lymphogranuloma venerum (LGV) (4%). Sixteen (64.0%) of the CSWs with herpes genitalis had HIV-1 infection. The risk ratio of herpes genitalis for HIV acquisition was 3.0 (95% CI: 2.0 - 4.4). Syphilis and chancroid were also found tobe significantly associated with increased risk of HIV infection (p < 0.0001). The adjusted odd ratios for Herpes genitalis, chancroid, and syphilis were 3.7 (1-13.0, p < 0.05), 19.8 (2.7-13.0, p < 0.05) and 19.1 (1-231.0, p < 0.05) respectively. There is need to educate FCSWs continually to adopt safer sexual behaviours, seek early diagnosis and treatment of GUDs to reduce their risk of transmitting HIV infection.